2015
DOI: 10.1017/s0007485315000012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of motility of carabid beetles in farmland

Abstract: Quantification of the movement of insects at field and landscape levels helps us to understand their ecology and ecological functions. We conducted a meta-analysis on movement of carabid beetles (Coleoptera: Carabidae), to identify key factors affecting movement and population redistribution. We characterize the rate of redistribution using motility μ (L2 T-1), which is a measure for diffusion of a population in space and time that is consistent with ecological diffusion theory and which can be used for upscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…Population redistribution in a homogeneous habitat can be modelled using Fokker‐Planck diffusion (Turchin, ; Ovaskainen, ), whereas behavioural responses to habitat interfaces can be modelled using preference indices (Cantrell & Cosner, ; Ovaskainen & Cornell, ; Maciel & Lutscher, ). The parameter representing the rate of population spread in a Fokker‐Planck modelling framework is denoted as motility with unit m 2 day −1 (Turchin, ; Allema et al, ). Motility in the Fokker‐Planck equation is similar to diffusivity in the Fickian diffusion model, but whereas diffusion evens out differences in density between adjacent habitats, even if the diffusivity is spatially heterogeneous, the same is not the case for a Fokker‐Planck model (Turchin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Population redistribution in a homogeneous habitat can be modelled using Fokker‐Planck diffusion (Turchin, ; Ovaskainen, ), whereas behavioural responses to habitat interfaces can be modelled using preference indices (Cantrell & Cosner, ; Ovaskainen & Cornell, ; Maciel & Lutscher, ). The parameter representing the rate of population spread in a Fokker‐Planck modelling framework is denoted as motility with unit m 2 day −1 (Turchin, ; Allema et al, ). Motility in the Fokker‐Planck equation is similar to diffusivity in the Fickian diffusion model, but whereas diffusion evens out differences in density between adjacent habitats, even if the diffusivity is spatially heterogeneous, the same is not the case for a Fokker‐Planck model (Turchin, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence that insect activity can depend on habitat structure, for example, the meta‐analysis by Allema et al. () showed that mobility rates of Carabid beetles (Carabidae) is approximately 5.6 times as high in farmland as in woody habitat. In particular, those species associated with forested habitats had greater mobility than those associated with open field habitats, both in arable land and woody habitat.…”
Section: Resultsmentioning
confidence: 99%
“…high dispersal rates have been recorded for Carabid beetles (Coleoptera: Carabidae) in farmland in contrast to lower rates measured in woody habitats, see table 2 in Allema et al. (). Capture rates are strongly influenced if the movement paths are correlated, i.e. if insects exhibit memory, such as recollection of previous locations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dispersal (i.e., the spatial redistribution of populations) is one of the most significant components of entomological population ecology, behavioral ecology and conservation [ 1 4 ]. Because dispersal is (in part) random movement of individuals, which underlies the redistribution in space of a population [ 5 – 8 ], there is a close relationship between movement (i.e., the spatial behavior of individuals) and dispersal. Movement of insects is of central importance for them to avoid natural enemies [ 9 ], search for food [ 10 , 11 ], secure mates [ 12 ], and find suitable habitats [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%